Ar Rahman-Based Dysmenorrhea Gymnastic to Reduce Pain - Sri Sumaryani; Praditiana Indah Puspita Sari (Jurnal Ners, 2015)
Introduction: More than 50% dysmenorrhea are caused by excessive amounts of prostaglandin hormone during menstruation.  The combination of dysmenorrhea gymnastics and Qur'an Surah Ar-Rahman relaxation techniques is a new innovation in non-pharmacological therapy to overcome dysmenorrhoea. The purpose of this study was to determine the level of pain differences on respondents who were given dysmenorrhea gymnastics treatment, Al Quran Surah Ar-Rahman recitation, and dysmenorrhea gymnastics combined  with Al Quran Surah Ar-Rahman recitation. Method: The research was conducted from March to May 2015 with quasi-experimental pretest-posttest control group design. The samples were 62 respondents, divided into 3 groups: 18 respondents in group of dismenorrhea gymnastic, 23 respondents in group of  Al-Qur an Surah Ar-Rahman, and  21 respondents in group of dismenorrhea gymnastic combined with Al Quran Surah Ar-Rahman recitation. Statistical test used wilcoxon and kruskal wallis test with significance level α <0.05.Result: The results showed that the Ar Rahman-based dysmenorrhea gymnastics statistically  proven can reduce menstrual pain more effectively compared with other interventions: menstrual gymnastics only and murrotal only,  with p = 0.001 and the mean rank pre intervention is 31,31, and mean rank post intervention is 19,50.Discussion: Nurses may give non pharmacologic alternative therapies to reduce dysmenorrhea by providing intervention Ar Rahman-based dysmenorrhea gymnastic.